Getting Intelligence Into the Minds of People (LEARNing Landscapes, 2013)
In conversation, Seymour Papert once asked me, "What’s the point of studying Artificial Intelligence if not to get intelligence into the minds of people?" His question inspires my juxtaposition of explorations of Natural Learning and Constructed Personal Knowledge. Since "you can’t learn about learning without learning about learning something,"1 the analyses will proceed with two examples. The first, focused on strategy learning at tic-tac-toe, concludes that learning depends on specific relationships among the elements of the context in interaction with processes of incremental cognitive change. The second analysis, focused on mastering a solution for Rubik’s Cube, argues the importance of reformulation of representations as a strategy for learning in more complex situations, and that the integration of multiple modalities of representation can be a key to "getting the intelligence into the minds of people."
Keywords: Natural Learning; Constructed Personal Knowledge; learning; learning about learning; strategy learning; context; intelligence; mind